Different AIDS incubation periods and their impacts on reconstructing human immunodeficiency virus epidemics and projecting AIDS incidence. - Bacchetti, P (1993)
The objective of this study was to investigate heterogeneity in incubation distributions in different cohorts and to assess the sensitivity of back-calculated infection rates to different assumptions about incubation times from human immunodeficiency virus (HIV) infection to AIDS diagnosis. Incubation distributions were estimated by using data from three different cohort studies. These and one other published incubation model were used as inputs for a back-calculation procedure that reconstructed smooth HIV-infection rates from AIDS incidence among adults in the United States, allowing for changes over time in incubation. Incubation estimates from the different cohorts differed substantially. The cumulative HIV incidence estimates that result from using the different incubations are very different, but the back-calculated models all produce good fits to the observed diagnosis counts. We conclude that systematic differences in incubation times of different groups add substantially to the uncertainty inherent in using the back-calculation method to reconstruct HIV epidemics and project future numbers of AIDS cases.